The structure of Rpf2-Rrs1 explains its role in ribosome biogenesis - Kharde, Satyavati; Calviño, Fabiola R.; Gumiero, Andrea; Wild, Klemens; Sinning, Irmgard (Nucleic acids research, 2015)
Abstract. The assembly of eukaryotic ribosomes is a hierarchical process involving about 200 biogenesis factors and a series of remodeling steps. The 5S RNP co